Effect of Exchange Rate Shock on Key Sectors of the Nigerian Economy - Onyebuchi Iwegbu; Isaac Chiawolam Nwaogwugwu (Leading Issues in Macroeconomic Stabilisation and Financial Development, A Festschrift in Honour of Professor Oluwatayo Fakiyesi, 2019)
This study conducts a comparative analysis of the effect of exchange rate shock on the industrial and agricultural sector in the regulated regime and the guided deregulated regime in Nigeria. The study employs a Structural Vector Autoregression (SVAR) to estimate the shock with the aid of SVAR Forecast Error Decomposition (FEVDs) and the Structural Impulse-Response Function. Preliminary tests reveal that the variables employed were integrated at varying order of level and first difference and further test revealed a bound long run co-integration on the models specified. From the study, it was discovered that in the regulated regime, agricultural output and industrial sector output fairly did not respond to exchange rate shocks both in the short run and in the long run. However, in the guided deregulated regime, exchange rate shock in the long run negatively affects the industrial sector more than the agricultural sector. Another conclusion drawn from the study is that most of the shocks in the agricultural and industrial sector are primarily caused by exchange rate shocks. The policy implication therefore is that any shock in a deregulated exchange rate system greatly affects the industrial sector than the agricultural sector in the long run. Further policy implication from the study is that agricultural and industrial sector shocks are basically caused by exchange rate shocks in a deregulated regime than a regulated regime as monetary policy is the main thrust of shocks in both sectors in the regulated regime.
Keywords: F31; 330; Exchange Rate Shock; Industrial Sector; Agricultural Sector; Structural Vector Autoregression (SVAR)